Institutional and Policy Analysis of River Basin Management : The Murray Darling River Basin, Australia - Blomquist, William (World Bank, Washington, DC, 2012)
The authors describe and analyze management in the Murray-Darling basin of Australia, long regarded as a model for integrated river basin management. This interior basin of over 1 million k